A Systematic Review of Chuna Manual Therapy for Adolescent Idiopathic Scoliosis - Ga Hyeon Jung; Hyun Lee; Hae Jin Kong; Hwa Yeon Ryu; Yong Ho Ku; Jae Hui Kang (MEDrang Inc., 2019)
This study analyzed randomized controlled trials (RCTs) and case studies investigating Chuna manual therapy and variations of this term, for adolescent idiopathic scoliosis. On June 15th, 2019, 6 online databases were used to retrieve studies. A total of 527 articles were retrieved, and 14 RCTs and 20 case studies were selected for review. Typically, the frequency of Chuna therapy was 1-2 times/week. The most common period of treatment was 12 months in RCTs and 3-6 months in case studies. Cobb's angle was the most frequent evaluation index used (11 RCTs and 20 case studies). In control groups, brace treatment was used in 8 RCTs. In 6 RCTs and 20 case studies, Cobb's angle significantly decreased after Chuna therapy, and in 4 RCTs, Chuna therapy was as effective as brace treatment, with no significant difference between groups. Adverse events were not reported except for minor reactions in only 3 case studies. This review suggested that Chuna therapy for adolescent idiopathic scoliosis was more advantageous than and as effective as brace treatment in most cases, although the risk of bias in 13 RCTs was unclear.